1974
DOI: 10.1128/jb.119.3.913-922.1974
|View full text |Cite
|
Sign up to set email alerts
|

Surface Polysaccharide from Staphylococcus aureus M That Contains Taurine, d -Aminogalacturonic Acid, and d -Fucosamine

Abstract: The surface polysaccharide antigen of Staphylococcus aureus M was isolated, and the component parts were identified. The antigen is composed of taurine, d -aminogalacturonic acid, and d -fucosamine. The capsule is chemically distinct from all previously reported staphylococcal capsules. Taurine and aminogalacturonic acid have not been reported previously in staphylococci.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

1976
1976
1992
1992

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(23 citation statements)
references
References 29 publications
2
21
0
Order By: Relevance
“…However, our title indicates that our investigation was limited to unencapsulated strains. Liau et al (14) found that their strain M of S. aureus contained taurine, D-aminogalacturonic acid, and r-fucosamine. In our unencapsulated strains we detected only a trace of Lufucose.…”
Section: Resultsmentioning
confidence: 99%
“…However, our title indicates that our investigation was limited to unencapsulated strains. Liau et al (14) found that their strain M of S. aureus contained taurine, D-aminogalacturonic acid, and r-fucosamine. In our unencapsulated strains we detected only a trace of Lufucose.…”
Section: Resultsmentioning
confidence: 99%
“…Incorporation into polysaccharides produces a negatively charged capsule surface. Antigenic polysaccharides consist of taurine, D-fucosamine, and D-aminogalacturonate from which taurine can be released by mild hydrolysis (455).…”
Section: Other Taurine Metabolitesmentioning
confidence: 99%
“…Aminouronic acids are uncommon among the CPS of pathogens (20). The CPS of Salmonella typhi (Vi) and of Staphylococcus aureus, however, contain aminouronic acids (12,16,23,48). Since we were interested also in synthesizing conjugates with the CPS of invasive S. aureus, which are difficult to obtain in high yield, we used Pn12F as a model.…”
mentioning
confidence: 99%